0 - Editorial - journal system, (African Sociological Review, 2018)
This issue of the journal lends itself to papers focused on gender, feminism and women. On one hand, it is a deliberate editorial decision. It is not often that the journal has over 45% of the papers in one issue on such matters, in French and English. To this extent, the editorial decision is deliberate. However, it needs to be stressed that in the course of the past eighteen months, there has been an increased number of papers submitted to the journal that focus on gender, feminism and women. This is well over 30% of submitted papers during this period. 55% of these papers were reviewed favourably and accepted for publication. It is therefore inevitable that an issue will contain papers focused on gender, feminism and women at one point in the journal’s publishing cycle. The papers in the current issue of the journal are reflective, empirical and historical, thus contributing to the immense literature on gender, feminism and women in Africa. Olajide Oloyede Managing Editor